Optimized methods for the targeted surveillance of extended-spectrum beta-lactamase-producing Escherichia coli in human stool - Sarah Gallichan; Sally Forrest; Esther Picton-Barlow; Claudia McKeown; Maria Moore; Eva Heinz; Nicholas A. Feasey; Joseph M. Lewis; Fabrice E. Graf (Microbiology Spectrum)
ABSTRACT Understanding transmission pathways of important opportunistic, drug-resistant pathogens, such as extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli, is essential to implementing targeted prevention strategies to interrupt transmission and reduce the number of infections. To link transmission of ESBL-producing E. coli (ESBL-EC) between two sources, single-nucleotide resolution of E. coli strains, as well as E. coli diversity within and between samples, is required. However, the microbiological methods to best track these pathogens are unclear. Here, we compared different steps in the microbiological workflow to determine the impact different pre-enrichment broths, pre-enrichment incubation times, selection in pre-enrichment, selective plating, and DNA extraction methods had on recovering ESBL-EC from human stool samples, with the aim to acquire high-quality DNA for sequencing and genomic epidemiology. We demonstrate that using a 4-h pre-enrichment in Buffered Peptone Water, plating on cefotaxime-supplemented MacConkey agar and extracting DNA using Lucigen MasterPure DNA Purification kit improves the recovery of ESBL-EC from human stool and produced high-quality DNA for whole-genome sequencing. We conclude that our optimized workflow can be applied for single-nucleotide variant analysis of an ESBL-EC from stool.IMPORTANCEDrug-resistant infections are increasingly difficult to treat with antibiotics. Preventing infections is thus highly beneficial. To do this, we need to understand how drug-resistant bacteria spread to take action to stop infection and transmission. This requires us to accurately trace these bacteria between different sources. In this study, we compared different laboratory methods to see which worked best for detecting extended-spectrum beta-lactamase (ESBL)-producing E. coli, a common cause of urinary tract or bloodstream infections, from human stool samples. We found that enriching stool in a nutrient broth for 4 h, then plating the bacterial suspension on antibiotic-selective MacConkey agar, and finally extracting DNA from the bacteria using a specific DNA purification kit resulted in improved recovery of ESBL E. coli and high-quality DNA. Sequencing multiple isolates from stool allowed us to distinguish unambiguously and at high resolution between different variants of ESBL E. coli present in stool.